Kesulitan Berbicara Pada Penderita Bibir Sumbing Tiktoker Slamet: Kajian Psikolinguistik - Saputri, Dessy; Putri, Reni Anisa; Habibah, Ulul; Nadifah, Adelia; Shobir, Indra Bahru (Universitas Negeri Padang, 2025)
This study aims to analyze the speech difficulties experienced by TikToker Slamet with a cleft lip based on a psycholinguistic study. The research method used is descriptive qualitative with data sources in the form of three videos with a total duration of 3 minutes 9 seconds. Data were analyzed through word-by-word pronunciation observations which were then classified based on word type (noun, verb, adjective, adverb) and phoneme type (vowel and consonant). The results showed that the main disorders were found in bilabial consonant phonemes (/p/, /b/), alveolar (/t/, /d/), and velar (/k/, /g/). These findings support Levelt's (1989) speech production theory and the SPARC model (Cho et al., 2024) which emphasize the importance of spatial-temporal coordination of the articulatory organs. Psycholinguistically, Slamet's cognitive language abilities were not impaired, but physiologically he experienced articulatory difficulties. These findings demonstrate the integration of physical, cognitive, and psychosocial aspects in the language production of cleft lip sufferers. Keywords: Language, Psycholinguistics, Phonemes